2020
DOI: 10.3389/fgene.2020.491895
|View full text |Cite
|
Sign up to set email alerts
|

How Can Drug Metabolism and Transporter Genetics Inform Psychotropic Prescribing?

Abstract: Many genetic variants in drug metabolizing enzymes and transporters have been shown to be relevant for treating psychiatric disorders. Associations are strong enough to feature on drug labels and for prescribing guidelines based on such data. A range of commercial tests are available; however, there is variability in included genetic variants, methodology, and interpretation. We herein provide relevant background for understanding clinical associations with specific variants, other factors that are relevant to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 581 publications
(663 reference statements)
0
23
0
1
Order By: Relevance
“…Pharmacoscan includes rs1061235 as a screen for HLA-A*31:01 as well. Cross-validation of our method could be undertaken versus the multiple technologies above described in a manner that we have previously described (Carvalho Henriques, et al, 2020a;2020c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacoscan includes rs1061235 as a screen for HLA-A*31:01 as well. Cross-validation of our method could be undertaken versus the multiple technologies above described in a manner that we have previously described (Carvalho Henriques, et al, 2020a;2020c).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the HLA haplotypes HLA-B*15:02 and HLA-A*31:01 are predictive of severe cutaneous reactions to the anticonvulsant drug carbamazepine, also prescribed as a mood stabilizer in psychiatry ( Fan et al, 2017 ; Gui et al, 2018 ; Carvalho Henriques et al, 2020c ). Cutaneous ADRs are one of the most common types of ADRs, typically occur in the first two to three months of drug use, and can range from a mild skin rash to a life-threatening reaction such as Stevens-Johnson syndrome and the more severe form of this, known as toxic epidermal necrolysis (SJS/TEN).…”
Section: Introductionmentioning
confidence: 99%
“…Many antidepressants, atomoxetine, and several antipsychotics are metabolized by CYP2D6 and CYP2C19 [1][2][3][4][5][6][7]. The gene (CYP2D6) encoding the enzyme CYP2D6 is on chromosome 22q13.2 [8] adjacent to two pseudogenes, CYP2D7 and CYP2D8 [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Different CYP2D6 or CYP2C19 haplotypes may be associated with different levels of enzyme activity, ranging from loss-offunction haplotypes (which give rise to no functional enzyme), to haplotypes with decreased function (which are associated with an enzyme with reduced metabolic activity), to gain-of-function haplotypes (associated with increased activity) [4]. Haplotype frequencies vary between and within ethnic groups [1,4,[28][29][30][31]. The study of clinical associations between variants in these genes and response to relevant medications has been to date limited by the challenging nature of the genotyping, particularly in the case of CYP2D6 [32].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent data do indicate that preemptive genotyping for CYP2C19 and CYP2D6 has promise and the specific phenotypes based on genotyping are related to the observed pharmacokinetics of antipsychotic and antidepressant drugs and also to the likelihood of switching drugs during the treatment (Jukic et al, 2019;van Westrhenen et al, 2020;Carvalho Henriques et al, 2020;Islam et al, 2021). Furthermore, after evaluation of 1,159 studies Karamperis et al found that only CYP2C19 and CYP2D6 drug gene associations did exhibit cost benefit in psychiatric pharmacogenomics (Karamperis et al, 2021).…”
Section: Editorial On the Research Topic From Trial And Error To Individualised Pharmacogenomics-based Pharmacotherapy In Psychiatrymentioning
confidence: 99%